ANALOGUE MODELS OF MELT-FLOW NETWORKS IN FOLDING MIGMATITES - Barraud J.; Gardien V.; Allemand P.; Grandjean P. (My University, 2004)
We have modelled the formation and the layer-parallel shortening of layered (stromatic) migmatites. The model consists of thin superposed layers of partially molten microcrystalline wax. The melt (30 vol.%) has a negative buoyancy and a high viscosity contrast with its solid matrix. As soon as the shortening begins, melt-filled veins with high aspect ratios open along foliation. The melt is segregated into the veins, forming a stromatic layering. During incipient folding, crescent-shaped saddle reefs open at the hinges of open sinusoidal folds. Further shortening and melt-enhanced shear displacements on interlayer interfaces cause chevron folds to develop and the saddle reefs to become triangular. In comparison, a melt-free experiment shows only a few layer-parallel openings and no saddle reefs in chevron folds. On the basis of our experimental results, we propose that in migmatites: (1) mesoscale melt migration is a combination of flow in immobile veins and movements of veins as a whole; (2) the changes in the geometry of the mesoscale melt-flow network create the pressure gradients that drive melt migration; (3) the melt-flow network does not need to be fully interconnected to allow local expulsion; (4) melt expulsion is episodic because the temporal evolution of the network combines with the spatial heterogeneity of the deformation.
Keywords: Migmatites; Melt segregation; Melt migration; Compaction; Leucosomes; Folds; Paraffin wax